AMF inoculation reduces yield losses in rice exposed to alternate wetting and drying and low fertilization - Daouda Mbodj; Abdala Gamby Diedhiou; Baboucarr Manneh; Cheikh Ndiaye; Laurent Laplaze; Aboubacry Kane (Scientific Reports)
Abstract Arbuscular mycorrhizal fungi (AMF) enhance the uptake of water and nutrients by host plants. In this study, we examined the response of six rice varieties from two ecotypes (three irrigated and three rainfed upland varieties) to AMF inoculation at five fertilizer levels, under continuous flooding (CF) and alternate wetting and drying (AWD) irrigation over two consecutive years in field conditions. Both irrigated and upland rice varieties experienced significant yield losses with AWD irrigation and reduced NPK fertilizer levels, with irrigated rice being more severely affected. Under AWD irrigation, AMF inoculation mitigated relative yield losses, especially when half of the recommended fertilizer dose was applied. In CF conditions, AMF inoculation often fully compensated for yield losses caused by reduced NPK levels. Furthermore, irrigation regime, fertilizer levels, and ecotype were significant sources of variation in the effects of AMF inoculation on several yield-related traits, such as total biomass, tiller number, panicle number, fertility, and maturity dates. Our findings suggest that AMF inoculation could be integrated with AWD irrigation and/or low NPK inputs to contribute to fertilizer and water savings in both irrigated and upland rice production systems.